H1N1 and WW1: The Spanish flu and the great war - Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2024)
World War 1 exacerbated the cost of the influenza epidemic of 1918-19 in two ways. First, it facilitated the spread the flu virus through the movement of clusters of infected soldiers and sailors. Second, it constrained public health measures that would have reduced mortality (as during the Covid-19 epidemic). While there is no obvious way of estimating any resulting mortality, attributing even a modest share of the deaths caused by the flu to the war would significantly increase the civilian death toll.
Keywords: N30; I18; 330; pandemic; influenza; World War I